2011
DOI: 10.1007/s10552-011-9779-7
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and tobacco, and the risk of cancers of the upper aerodigestive tract in Latin America: a case–control study

Abstract: In this largest study on UADT cancer in Latin America, we have shown for the first time that a prevailing majority of UADT cancer cases is due to a combined effect of alcohol and tobacco use and could be prevented by quitting the use of either of these two agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 17 publications
5
34
0
11
Order By: Relevance
“…Actions to prevent sunlight-related squamous cell carcinoma of the lip are as important as those directed towards tobacco and alcohol consumption, which increase the risk of oral squamous cell carcinoma by 5.49 and 4.62 times, respectively. 16 The percentage of malignant lesions (9.4%) found by the present study was similar to those found by other studies conducted in the Brazilian Northeast. 17 An exception was the predominance of lip cancer (57.1%) over intraoral cancer, which was most likely due to the large number of study participants who were exposed daily to ultraviolet radiation.…”
Section: Discussionsupporting
confidence: 92%
“…Actions to prevent sunlight-related squamous cell carcinoma of the lip are as important as those directed towards tobacco and alcohol consumption, which increase the risk of oral squamous cell carcinoma by 5.49 and 4.62 times, respectively. 16 The percentage of malignant lesions (9.4%) found by the present study was similar to those found by other studies conducted in the Brazilian Northeast. 17 An exception was the predominance of lip cancer (57.1%) over intraoral cancer, which was most likely due to the large number of study participants who were exposed daily to ultraviolet radiation.…”
Section: Discussionsupporting
confidence: 92%
“…The etiologic factors strongly associated with the development of OSCC are the consumption of tobacco and alcohol (3,4). However, in recent decades, there has been an increasing trend of OSCC development in females and young adults, for whom other etiological factors like genetic heritage, dietary habits and Human Papilomavirus (HPV) infection have been pointed out as causes (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Although alcoholic consumption is often cited as a known risk factor of oral cavity cancer (Altieri et al, 2004;Scully, 2011;Szymańska et al, 2011), some studies did find alcohol was not associated with an elevated risk of oral cavity cancer (Takács et al, 2011;Yen et al, 2008). One possible explanation for the seeming contradiction may be that different studies defined alcohol consumption differently.…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…Many studies have found that there is a synergic effect of cigarette smoking, alcoholic consumption, and betel quid chewing in carcinogenesis of oral cavity mucosa (Castellsagué et al, 2004;Chang et al, 2001;Ko et al, 1995;Szymańska et al, 2011;Wen et al, 2010;Yen et al, 2008). Patients who smoked and also consumed alcohol had an odds ratio of 9.03 for contracting oral cavity cancers, whereas patients who only smoke or only consumed alcohol had odds ratios of 4.65 and 0.95, respectively when compared with abstainers (Yen et al, 2008).…”
Section: Synergistic Effectmentioning
confidence: 99%